Development and validation of SuperDEM for non-spherical particulate systems using a superquadric particle method - Gao, Xi (2022)
This article presents the development and validation of the Superquadric Discrete Element Method (SuperDEM) for non-spherical particle simulation using a superquadric particle method in open-source CFD suite MFiX. A superquadric particle-particle contact algorithm with accelerating and stabilizing strategy was developed. A superquadric particle-arbitrary wall contact algorithm was developed, which enables the simulation in complex geometry. The solver was validated by comparing with experimental data generated in this study or available in the literature. Tests include cylinder contacting with a wall, static packing of M&M chocolate candies in a cylindrical container, static packing of cylinders in a cylin-drical container, dynamic angle of repose of cylinders in a rotating drum, and discharging of chocolate candies from a hopper. Besides, MPI parallelization of the solver was implemented and the parallel per-formance of the solver using MPI was assessed through large-scale simulations of 1 million, 10 million, and 100 million particles on up to 6800 cores, which demonstrates that the SuperDEM solver has great potential for industrial-scale systems simulation. (c) 2021 Chinese Society of Particuology and Institute of Process Engineering, Chinese Academy of Sciences.